1980
DOI: 10.1111/j.1432-1033.1980.tb04432.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Oligosaccharides from Human Erythrocyte Membranes of Different Blood-Group-P Phenotypes by Trifluoroacetolysis

Abstract: Human erythrocyte membranes of different blood-group-P phenotypes have been degraded by trifluoroacct olysis at conditions that will effect transamidation. This degradation resulted in dissolution of the membranes with concomitant degradation of proteins. Oligosaccharide chains linked to proteins and ceramides were released as their pertrifluoroacetylated derivatives, which generally are stable towards further action of the reagent. 2-Acetamido-2-deoxy-sugar residues were converted into their corresponding 2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Interestingly, chemical and immunochemical studies have indicated that galabiosylceramide and P 1 and P k antigens are expressed in many pig and human tissues (73,(77)(78)(79). In addition, several studies have shown that Gal␣1-4Gal-containing glycolipids act as receptors for the binding of pathogenic bacteria, such as Escherichia coli to human uroepithelial cells (79) and Streptococcus suis, which is responsible for meningitis in pigs and humans (80,81).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, chemical and immunochemical studies have indicated that galabiosylceramide and P 1 and P k antigens are expressed in many pig and human tissues (73,(77)(78)(79). In addition, several studies have shown that Gal␣1-4Gal-containing glycolipids act as receptors for the binding of pathogenic bacteria, such as Escherichia coli to human uroepithelial cells (79) and Streptococcus suis, which is responsible for meningitis in pigs and humans (80,81).…”
Section: Discussionmentioning
confidence: 99%
“…39 O-trifluoroacetylation is complete and amino functions are all N-trifluoroacetylated. N-Acetyl groups undergo transamidation to N-trifluoroacetyl groups but sialic acid residues are hydrolyzed from the gangliosides.…”
Section: Isolation Of Oligosaccharide Chainsmentioning
confidence: 99%